Utility of Papanicolaou test in diagnosis of cervical lesions: a study in a tertiary care centre of western Uttar Pradesh - Bisht, Mithila; Agarwal, Shweta; Upadhyay, Deepak (International Journal of Research in Medical Sciences, 2017)
Background: Cervical cancer is the most common cancer among females in India. It is also one of the major causes of deaths among them. Papanicolaou (Pap) cytological test helps in detecting the early epithelial abnormalities in cervical cells. The morbidity and mortality due to cervical cancer has come down in countries with well-established screening programmes at national level. This study was conducted to emphasize the value of cervical screening as a tool for early detection of non-neoplastic and neoplastic lesions of cervix. Slide positivity rate was computed and clinico-pathological correlation was done. Methods: This cross-sectional study was conducted from January 2012 to December 2014 (3 years), on 2202 women aged between 20-70 years coming for a Pap smear examination in a tertiary care hospital in Bareilly, India. After staining with conventional Papanicolaou technique, all cases were classified as per Bethesda nomenclature (2001). Results: Out of 2202 cases, 85.16% slides were found to be negative for intraepithelial abnormalities and 14.84% slides were labelled as positive for epithelial lesions. 97.67% of high grade lesions were found in women more than 40 years. Smears with epithelial cell abnormality were found more common in older age groups whereas smears negative for epithelial cell abnormality were found more common in young age groups. Conclusion: Pap test is a cost effective cancer screening and is a simple method to detect various lesions of cervix, non-neoplastic as well as neoplastic. High risk screening programmes should be directed to all women >40 years. Pap test is especially useful to diagnose precancerous lesions of cervix, thereby early detection of these lesions & subsequent proper treatment can be helpful in prevention of cervical cancer.